The Mount McKinley region, Alaska, by Alfred H. Brooks; with descriptions of the igneous rocks and of the Bonnifield and Kantishna districts, by L.M. Prindle. - Brooks, Alfred H. 1871-1924. (Professional paper (Geological Survey (U.S.)), 1911)
Report of 1902 exploratory journey from Pacific seaboard through Alaska Range along northwest base of Mount McKinley to Tanana and Yukon rivers. Includes concise summary of mineral wealth of region and description of stratigraphy, structure, and geologic history of area. Also contains information about climate, vegetation and wildlife, agricultural lands, and means of communication and transportation.